Enhanced splenic volume and contraction in elite endurance athletes - Holmström, P. K.; Karlsson, Ö.; Lindblom, H.; McGawley, K.; Schagatay, E. K. (Journal of Applied Physiology, 2021)
Splenic contraction, which leads to ejection of stored erythrocytes, is greater in athletes involved in regular freediving or high-altitude activities. As this response facilitates oxygen-carrying capacity, similar characteristics may be expected of elite endurance athletes. Therefore, our aims were to compare resting and apnea-induced splenic volume in endurance athletes and untrained individuals, and to assess the athletes` exercise-induced splenic volume. Twelve elite biathletes (7 women) and 12 controls (6 women) performed a maximal effort apnea in a seated position. In addition, the biathletes completed a maximal roller-skiing time trial. Splenic dimensions were measured by ultrasonic imaging for subsequent volume calculations, whereas Hb was analyzed from capillary blood samples and cardiorespiratory variables were monitored continuously. Baseline splenic volume was larger in the biathletes (214 ± 56 mL) compared with controls (157 ± 39 mL, P = 0.008) and apnea-induced splenic contraction was also greater in the biathletes (46 ± 20 mL vs. 30 ± 16 mL, P = 0.035). Hb increased immediately after apnea in the biathletes (4.5 ± 4.8%, P = 0.029) but not in the controls (-0.7 ± 3.1%, P = 0.999). Increases in exercise-induced splenic contraction (P = 0.008) and Hb (P = 0.001) were greater compared with the apnea-induced responses among the athletes. Baseline splenic volume tended to be correlated with Vo2max (r = 0.584, P = 0.059). We conclude that elite biathletes have greater splenic volume with a greater ability to contract and elevate Hb compared with untrained individuals. These characteristics may transiently enhance O2-carrying capacity and possibly increase O2 uptake, thereby helping biathletes to cope with high intermittent O2 demands and severe O2 deficits that occur during biathlon training and competition.